Interfacial Area between Hetero‐Epitaxial γ‐Al2O3 and Silicon. Issue 17 (13th July 2017) - Liao, Yuanxun; Zhou, Dongyi; Shrestha, Santosh; Huang, Shujuan; Bremner, Stephen; Conibeer, Gavin
Abstract : The interfacial region between hetero‐epitaxial γ‐Al2 O3 and Si (111) substrates is studied in detail. The purpose is to address many open questions regarding the growth of γ‐Al2 O3 grown on Si, such as the atomic stacking orders, strain relaxation modes, and observed thin‐film qualities. The cross‐sectional atomic stacking order is directly evidenced to be a cubic spinel structure, with a possible in‐plane stacking order proposed. A 1.5 nm defect‐rich transition layer is found at the interface, in which the lattice structure transitions from Si to γ‐Al2 O3 arrangement. The thin‐film quality, in terms of crystallinity and low film roughness, is observed to improve with increasing thickness up to ≈8 nm. For thicknesses above 8 nm, grain boundaries are observed along with the appearance of pinholes, due to the large lattice constant and thermal expansion coefficient differences between γ‐Al2 O3 and Si. Polycrystalline islands form in these pinholes and gradually replace the initial layer‐by‐layer growth of monocrystalline γ‐Al2 O3, leading to a mainly polycrystalline material at large thicknesses. The insights gained on the hetero‐epitaxy of γ‐Al2 O3 on Si will be useful for future work looking to exploit this hetero‐epitaxial materials system. Abstract : High‐quality hetero‐epitaxial γ‐Al2 O3 on Si (111) is achieved with pulsed laser deposition, whose atom stacking orders are directly evidenced to be consistent with cubic spinel structures. An interfacial layer reveals the transition of atoms from γ‐Al2 O3 to Si arrangements. Film quality degrades when layer‐by‐layer growth changes to island formation due to the presence of pinholes.